The association between weight loss and long term development in quality-of-life among children living with obesity: a pragmatic descriptive intervention study - Rasmus Møller Jørgensen; Esben Thyssen Vestergaard; Britta Kremke; Rikke Frederiksen Bahnsen; Bent Windelborg Nielsen; Jens Meldgaard Bruun (BMC, 2022)
Abstract Background Childhood obesity is associated with impaired Quality-of-Life (QoL), increased stigmatization and higher risk of development of depression compared to their peers. This report describes the long-term development in QoL for cohort of children with obesity after a sustainable weight reduction. Methods This pragmatic descriptive intervention study enrolled 120 children with obesity, age 5-17 years, in a multifactorial lifestyle intervention. The intervention was an across sectors collaboration between a department of pediatrics and community health care workers. QoL was assessed yearly throughout the intervention and evaluated by a 6-item Visual Analogue Scale (VAS). For analyzing changes in VAS, as function BMI-SDS, regression models were used, while ANOVA and Wilcoxon test were applied for normal and not-normal distributed data. 95% confidence interval not containing 0 and p-value < 0.05 was considered statistically significant. Results After 26.4 months (13.9 SD) an overall decrease in bullying (0.6 vs. 0.0 median) and motivation (10.0 vs. 9.6) was observed. QoL increased in children with a BMI-SDS reduction (0.65 (2.49 SD)) opposite children with no-change or increasing BMI-SDS who reported reduced QoL (-0.36 (1.55 SD) and -0.96 (2.27 SD)). A significant inverse relationship was observed for Joy of Life, QoL and body perception as a function of BMI-SDS per year. Conclusion Weight reduction causes improvement in QoL for children with obesity and an inverse relationship for QoL and changing BMI-SDS / year was establish.